Renal-Biofunction Potentials of Ethanolic Extract of Solanum Melongena Linn Fruit on Monosodium Glutamate- Intoxicated Rats and Kidney Histology - Mbah, Uchendu O; Egbuonu, Anthony Cemaluk C; Nwanne, Ijere D; Jeremiah, Obinna (Journal of Diagnostics, 2019)
This study evaluated the renal biofunction potentials of ethanolic extract of Solanum melongena Linn fruit on monosodium glutamate-intoxicated rats’ and kidney histology using standard protocol. Twenty four Wistar rats that weighed 105.00 ± 7.00 g were used. The rats were assigned into 6 groups of 4 each and fed thus: Group 1 (control, feed and distilled water only), Group 2 (8000mg/kg body weight monosodium glutamate (MSG)), Group 3 (300mg/kg body weight (bw) the sample extract), Group 4 (8000mg/kg bw MSG + 100mg/kg bw the sample extract ), Group 5(8000mg/kg bw MSG+ 300mg/kg bw the sample extract) and Group 6 (8000mg/kg bw MSG+ 500mg/kg bw the sample extract) daily for 14 days. The results were expressed as mean ± S.E.M and one-way analysis of variance (ANOVA), followed by a Duncan posthoc test was done to test for significance using SPSS version 22.0. The exposure of MSG resulted in a significant (P =0.05) increase in the activities of serum urea, creatinine, potassium ion, chloride ion, and sodium ion compared to the control. MSG and ethanolic extract of Solanum melongena Linn fruit co-treated groups at different concentrations were significantly (P =0.05) reduced to become comparable to the control group. MSG consumption in high concentration alters renal biofunction and this is also evident in the histology of the studied rats’ kidney sections. However, the protective roles of ethanolic extract of Solanum melongena Linn fruit were notably at 500mg/kg of body weight in rats, a pointer to the dose-dependent function.